Current Approach of Corticosteroids Use in Ocular Therapy. - Dayamí Pérez Gómez; Ivonne González Parra; Francisco García González (Medisur)
Corticosteroids are a group of drugs widely used in ophthalmology through topical, intraocular, periocular or systemic administration. This wide use is caused by two of its major functions: anti-inflammatory and immunosuppressive actions. This study presents a review on this type of drugs, primarily in the area of ophthalmology. The goal is to deepen knowledge on this group of drugs, in order to make a best use of them. Aspects related to the type of administration of corticosteroids and the possible adverse reactions and drug interactions are included.